Performance-arte-vida: trocas e partilhas de/em experiências - Gilmara Gonçalves Oliveira (2021)
This dissertation presents the author's trajectory, as an artist-teacher-researcher in performance, how her experiences were crossed by the daily interaction with the environment in which she is inserted and the way she understands herself bodily in it. Along with this, a reflection is developed on how the practice of performance transforms those involved, as social subjects, due to reverberations during and after its realization, based on the personal experiences of the researcher, as an artist and teacher of this expression, in dialogue with various practices and studies in the field of performance art. In an autoethnographic exercise, past practices of the author are analyzed and interpreted, through traces of these artistic and pedagogical experiences, contained in logbooks and other documents of the researcher's process. As part and result of the research, it is shared, as a product of the same, the proposal of an artistic residency in performance-art life, in which people interested in bodily experiences in this expression may participate, having as a premise the understanding of their natures, through daily actions, always reflecting on the possible transformations in the subjects immersed in this practice.